The Effectiveness of Law Enforcement Against Online Gambling in the Digital Era in Medan City - Sunarto, Atika; Simarmata, Lucky Every; Maharani, Maharani; Adnan, Muhammad Ali (Journal of Law, Politic and Humanities, 2025)
This study aims to analyze the effectiveness of law enforcement against online gambling practices in the digital era, especially in Medan City, by reviewing the legal status of online gambling based on applicable laws and regulations, the impact of weak law enforcement, and efforts made by local law enforcement officers. The rampant cases of online gambling that are increasingly easily accessible through digital technology have caused social unrest as well as economic and moral losses in society. This study used a normative legal method with a legislative approach and literature study, and was supported by secondary data obtained through legal literature and official documents. The results of the study indicate that law enforcement in Medan City has not been running optimally because there are no regulations that specifically regulate online gambling, weak coordination between agencies, and a lack of supporting technological resources. Although enforcement efforts have been made by the police and related agencies, there are still many legal loopholes and technical limitations that are exploited by perpetrators to avoid legal entanglement. This study suggests the need for the formation of special regulations on online gambling, strengthening the digital capacity of law enforcement officers, and increasing public legal awareness as preventive measures in suppressing online gambling practices more effectively and sustainably.This research is relevant considering the importance of evaluating the extent to which positive law and law enforcement policies are capable of addressing the challenges of digital crimes, particularly online gambling.